Comparative ignition tests of coal under oxy-fuel conditions in a standardized laboratory test rig. (15th November 2017) - Becker, A.; Schiemann, M.; Scherer, V.; Shaddix, C.; Haxter, D.; Mayer, J.
Graphical abstract: Highlights: Good compromise between informative power and simple and reproducible processing. Tendencies known for the influence of O2 -concentration and coal rank are shown. Higher O2 -concentration in the atmosphere lead to lower ignition temperature. Higher volatile content in coal generally lead to lower ignition temperature. Conversion of this simple method to oxy-fuel environments has been successful. Abstract: Ignitability is important to characterize pulverized coal combustion, as it is directly related to flame stability. The current work describes a practical test rig for rapid laboratory analysis of pulverized coal cloud ignition properties. The system has been designed for conventional coal combustion conditions using air as the oxidant. In the current work, the measurement principle of the device is described and its adaption to and applicability for oxy-fuel combustion tests is demonstrated. Four coals with different rank were measured in air and in oxy-fuel atmospheres containing 20–35 vol% O2 in CO2 . The major influencing factors for the investigated samples were found to be the coal rank and the gas-phase oxygen concentration, while a minor influence of particle size was observed.